Exploring and understanding the locational strategic behaviour within the internationalisation of Chinese emerging multinational enterprises into developed economies - JONES, JONATHAN (2015)
Location advantages within the Internationalisation School of thought has greatly neglected location strategies in their regional intricacies and the implications of what benefits they could bring for emerging multinational enterprises. However, in order to do so, a theoretical framework based on the latest research needs to be established first to explain the phenomena that we may associate as locational factors occurring on the subnational level. It is only after this has been established that we may address the validity of the framework and explore further pertaining components that can be added to the location strategies framework. This piece of research sets off with the basis of what has been written in the literature so far, creating an ontology and epistemology for the consideration of location advantages at a subnational level, describing the flaws and gaps internationalisation theories and what implications governmental institutions can play in influencing location choices of EMNEs during the process of internationalisation. A multiple-case study method approach was utilised for three Chinese EMNEs: Lenovo, Huawei and Haier. These three companies were repeatedly compared to the theoretical framework to examine how robust this framework was able to explain and describe the considerations and exploitations taken by EMNEs during outward FDI behaviours.